2016
DOI: 10.17795/whb-38976
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Maternal Mortality and its Associated Causes at Shinyanga Regional Hospital in Tanzania

Abstract: Background: Maternal mortality remains a public health concern in low income countries particularly in sub-Saharan Africa where majority (62%) of maternal deaths occurs. In Tanzania maternal mortality ratio is as high as 432 deaths per 100,000 live births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Similar findings were recorded in a retrospective analysis of causes of health facility maternal deaths in Ogun state, Nigeria, and central regions of Kenya where haemorrhage was the leading cause accounting for 40% and 43.3%, respectively [ 6 , 11 ]. A study conducted at Shinyanga Regional Referral Hospital, Tanzania, also correlates to the above findings that haemorrhage was the leading cause of maternal deaths by 50% [ 12 ]. In another study, also conducted in Tanzania, Bwana et al found that haemorrhage was second to eclampsia in causing deaths at 24.6% [ 13 ].…”
Section: Discussionmentioning
confidence: 63%
“…Similar findings were recorded in a retrospective analysis of causes of health facility maternal deaths in Ogun state, Nigeria, and central regions of Kenya where haemorrhage was the leading cause accounting for 40% and 43.3%, respectively [ 6 , 11 ]. A study conducted at Shinyanga Regional Referral Hospital, Tanzania, also correlates to the above findings that haemorrhage was the leading cause of maternal deaths by 50% [ 12 ]. In another study, also conducted in Tanzania, Bwana et al found that haemorrhage was second to eclampsia in causing deaths at 24.6% [ 13 ].…”
Section: Discussionmentioning
confidence: 63%
“…In this analysis, 15 of the deceased were women who were para 5 and above. However, this finding does not correlate with those of Shinyanga Regional Referral Hospital and Muhimbili National Hospital (MNH) where the grand multipara made up 28.3 and 12.1, respectively [9,10]. This difference could be due to numbers of grand multipara becoming pregnant, especially for big cities like Dar es Salaam.…”
Section: Discussionmentioning
confidence: 83%
“…Many of the deceased were 35 years old and above, married, and peasants with no formal education. There were15 grand multipara followed by primigravida (9). Majority of them were admitted as referrals from other health facilities (32) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding shows that overall pregnancy-related mortality was high at 712 deaths per 100,000 live births. Nevertheless (Mapunda et al, 2016) conducted a study in Shinyanga regional referral hospital. The result indicated that maternal mortality ratio declined from 635/100,000 live births in 2010 to 449/100,000 live births in 2014 however observed maternal mortality ratio was higher compared to the national average.…”
Section: Maternal Mortality Situation In Tanzaniamentioning
confidence: 99%